Penerapan Perlindungan Hukum Hak Cipta Terhadap Seni Batik Riau di Pekanbaru - Aditya Taufan Nugraha (Jurnal Selat, 2014)
Indonesia is an archipelago with a variety of art and culture is very rich, the overall wealth of the nation is a potential that needs to be protected. The wealth of art and culture is a source of intellectual property that are given legal protection through legislation. one of the art treasures are protected Indonesian Batik Art. Copyright law protection against Batik Art by Article 12, letter i of Law Number 19 Year 2002 on Copyright. This protection is given as batik art as an intellectual work is a work that has artistic value in the creation of images or motifs or color composition. Wealth of art and culture in every area there in this nation, in addition to useful for the formation of character and dignity of the nation, also can be used to grow the creative economy. Pekanbaru as the capital of Riau province has a variety of art that is steeped in Malay culture, is one of the artistic diversity in creating the famous batik art batik wither. Keywords: Protection, Law, Baik Riau